PERSEPSI GURU MATA PELAJARAN PEMINATAN SOSIAL TERHADAP IMPLEMENTASI KURIKULUM 2013 REVISI DI SMA NEGERI 1 TELUKDALAM - Zendrato, Walsyukurniat (Institut Pendidikan Tapanuli Selatan, 2018)
According to the revised version of K13 implemented to X grade, a teacher is expected to follow the association training of K13 implementation to have knowledge about the implementation of K13.  The main problems in implementing the revised version of K13 faced by teachers of social sciences in senior high school areteachersâ willingness in implementing the curriculum, availability of course books for teachers and students, creativity in creating worksheets, assessment of studentsâ knowledge and skills, willingness to follow extra time of learning, and school report card.  Teachers face difficulties to get references and createworksheets becauseteachers are required to comprehensively study content ofpermendikbudthat sets the standard of competence of graduates, core competencies, and basic competence. Teachers encounter difficulties in determining operational verbs for indicator of competencies achievement and applying scoring system. The purposes of this research were to know how revised version of K13 is implemented in senior high school, teachersâ perception of social sciences concentration, andobstacles faced by teachers of social sciences concentration in implementing the curriculum. Qualitative approach with descriptive method wasapplied in this research.This research revealed that teachers of social sciences concentration have good and positive perception toward the implementation of revised version of K13. Based on the results, it is suggested that the principal of SMA N.1 Telukdalam should motivate the teachersin implementing revised version of K13, and the result of this research could be used as a reference byfurther researchers.